Model Kepemimpinan Guru SKI MTsN 9 Sleman dalam Meningkatkan Prestasi dan Motivasi Belajar Siswa - Muklis Cahyo Muh Arifin; Burhan Nudin (EL-TARBAWI, 2020)
This research originated from the emergence of students’ negative views on learning SKI (Islamic Cultural History). The leadership role of SKI teachers is expected to provide learning motivation so that it can improve student achievement. The purpose of this study is to analyze the application of leadership and explain the constraints of implementing the leadership of the SKI teachers in increasing student achievement and motivation. This research use desciptive qualitative approach. Data collection techniques are by observation, interviews and documentation. The research informants consisted of the vice chairman, the SKI teacher, and three students. This study found that teacher leadership can increase learning achievement and motivation. The process of applying leadership in learning, namely; 1) The teacher's introduction always begins with greetings, prayers, and motivation; 2) The core activity of learning is to use learning methods with interesting media; 3) In the closing activity, the teacher asks about the material that has been delivered and works on questions from the teacher. The process of implementing leadership outside of teacher learning always provides good examples such as student discipline and morals. Constraints faced by common are such as students lack of discipline in participating in learning, diverse characters, new methods that do not necessarily give satisfactory results. Meanwhile, the special obstacles faced were the lack of learning hours for the SKI, the lessons that were less attractive to students, and the differences in the educational background of the students.